Character of elastic energy absorption in well developed genetic-impurity defect structure in monocrystalline silicon - Gutsulyak, B.I.; Oliynych-Lysyuk, A.V.; Fodchuk, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Low-frequency internal friction and dynamic shear modulus (Geff) in Si monocrystal were investigated in the range of 20 to 200 ºC. Temperature hysteresis of internal friction was found and effective shear modulus was studied in the unirradiated and a series of irradiated silicon samples. The appearance of a hysteresis loop is due to interaction of genetic microdefects with crystal point defects and their nonsymmetric distribution in the process of samples heating-cooling.